Real-Time Facile Detection of the WO(3) Catalyst Oxidation State under Microwaves Using a Resonance Frequency - Tsubaki, Shuntaro (ACS Omega, 2020)
[Image: see text] Microwaves (MWs) are often used to enhance various heterogeneous catalytic reactions. Here, we demonstrate real-time monitoring of a catalyst’s oxidation state in a microwave catalytic reaction using a resonance frequency. The changes in the catalyst’s oxidation state during the reaction induced changes in the resonance frequency in the cavity resonator. The resonance frequency was not affected by 2-propanol adsorption, while the frequency decreased with the reduction of WO(3) → WO(3−x). That is, the redox state of the WO(3) catalyst could be detected using the resonance frequency. The oxidation state of the WO(3) catalyst was then directly observed by the resonance frequency during the dehydration reaction of 2-propanol by microwaves as a model reaction. Resonance frequency monitoring revealed that the enhanced dehydration of 2-propanol by microwaves was attributable to the reduction of the WO(3) catalyst. Moreover, the temporal changes in the oxidation state of the WO(3) catalyst detected by the resonance frequency coincided with that observed by operando Raman spectroscopy. Therefore, real-time resonance frequency monitoring allowed facile detection of the bulk catalyst oxidation state under microwaves without using any spectroscopic apparatus.